2008
DOI: 10.28945/128
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Information Culture on Adoption of a Self-Service System

Abstract: This article discusses a qualitative case study of adoption of a self-service based human resources management system in a utilities company by taking a perspective of information culture. The main finding is that a number of specific cultural aspects evolving around information technology and information can help to explain why the adoption of the system reached just a moderate level. Contributions of the study to understanding self-service information systems and to system adoption theory and practice are di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…These results were supported by the findings of Nam, Kim, and Jung's (2023) study, which concluded that, due to their lower levels of digital literacy, older individuals will continue to encounter difficulties when using SST. Similarly, technical issues that may arise during operation, such as insufficient programming usability, support or maintenance of obsolete equipment processes, slowed client aptitudes, and decreased system utilization, particularly during peak hours, have frequently pushed the buyer away (Travica, 2008;Ishak, 2021). Any negative experience, particularly in relation to SOKs, alters customers' perceptions of the technology, thereby severely limiting its use and adoption (Toh, 2018).…”
Section: Strongly Agree Total 329 Strongly Agreementioning
confidence: 99%
“…These results were supported by the findings of Nam, Kim, and Jung's (2023) study, which concluded that, due to their lower levels of digital literacy, older individuals will continue to encounter difficulties when using SST. Similarly, technical issues that may arise during operation, such as insufficient programming usability, support or maintenance of obsolete equipment processes, slowed client aptitudes, and decreased system utilization, particularly during peak hours, have frequently pushed the buyer away (Travica, 2008;Ishak, 2021). Any negative experience, particularly in relation to SOKs, alters customers' perceptions of the technology, thereby severely limiting its use and adoption (Toh, 2018).…”
Section: Strongly Agree Total 329 Strongly Agreementioning
confidence: 99%